Cerebellar Direct Current Stimulation (ctDCS) in the Treatment of Huntington's Disease: A Pilot Study and a Short Review of the Literature - Bocci, Tommaso; Baloscio, Davide; Ferrucci, Roberta; Sartucci, Ferdinando; Priori, Alberto (Frontiers in Neurology, 2020)
Introduction: in recent years, a growing body of literature has investigated the use of non-invasive brain stimulation (NIBS) techniques as a putative treatment in Huntington’s Disease (HD). Our aim was to evaluate the effects of cerebellar transcranial Direct Current Simulation (ctDCS) on the motor outcome in patients affected by HD, encompassing at the same time the current knowledge about the effects of NIBS both on motor and non-motor dysfunctions in HD. Materials and Methods: four patients (two females) were enrolled and underwent ctDCS (both anodal or sham, elapsed by at least three months: 2.0 mA, 20 min per day, 5 days a week). Clinical scores were assessed by using the Unified Huntington’s Disease Rating Scale – part I (UHDRS-I), immediately before ctDCS (T0), at the end of the 5-days treatment (T1) and 4 weeks later (T2). Results: anodal ctDCS improved motor scores compared to baseline (p = 0.0046), whereas sham stimulation left them unchanged (p = 0.33, Friedman test). In particular, following anodal ctDCS, UHDRS-I score significantly improved, especially regarding the subitem “dystonia”, both at T1 and T2 compared to sham condition (p < 0.05; Wilcoxon matched-pairs signed test). Conclusions: ctDCS improved motor scores in HD, with effects lasting for about 4 weeks after tDCS completion. This is the first study discussing the putative role of cerebellar non-invasive simulation for the treatment of HD.